2020
DOI: 10.1016/j.domaniend.2019.106432
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone and its receptor are detected in most gonadotropin-releasing-hormone cell bodies and fibers in heifer brains

Abstract: Circulating concentrations of Anti-Müllerian hormone (AMH) can indicate fertility in various animals, but the physiological mechanisms underlying the effect of AMH on fertility remain unknown. We recently discovered that AMH has extragonadal functions via its main receptor, AMH receptor type 2 (AMHR2). Specifically, AMH stimulates the secretion of luteinizing hormone and follicle stimulating hormone from bovine gonadotrophs. Moreover, gonadotrophs themselves express AMH to exert paracrine/autocrine functions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Interestingly, I recently reported that most cell bodies or fibers of GnRH-secreting neurons in the preoptic area, arcuate nucleus, and internal and external zones of the median eminence in the heifer hypothalamus express AMH [ 56 ]. Therefore, my recent data provide a new hypothesis ( Fig.…”
Section: Bovine Gonadotrophs Express Amhr2 and Amh To Regulate Lh Andmentioning
confidence: 99%
“…Interestingly, I recently reported that most cell bodies or fibers of GnRH-secreting neurons in the preoptic area, arcuate nucleus, and internal and external zones of the median eminence in the heifer hypothalamus express AMH [ 56 ]. Therefore, my recent data provide a new hypothesis ( Fig.…”
Section: Bovine Gonadotrophs Express Amhr2 and Amh To Regulate Lh Andmentioning
confidence: 99%
“…Moreover, recently, GnRH neurons in the areas of the brain relevant to neuroendocrine control of reproduction [the preoptic area (POA), arcuate nucleus (ARC), and median eminence (ME)] in humans and rodents were reported to express AMHR2 [ 2 ]. Additionally, we recently reported that 75–85% of cell bodies and fibers of bovine GnRH neurons are positive for both AMH and AMHR2 in the POA, ARC, and the internal and external zones of the ME [ 6 ]. Furthermore, AMH strongly activates GnRH neurons in adult female mice both in vivo and in vitro [ 2 ], and AMHR2-deficient mice showed abnormal development and function of GnRH neurons, which resulted in reduced fertility [ 11 ].…”
mentioning
confidence: 99%
“…We obtained POA and ARC&ME tissue samples based on the bovine brain atlas [ 10 , 14 ] using methods detailed in previous studies [ 3 , 6 ] and in Fig. 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations